Implementation of Private Television Policy Based on Broadcasting Regulation: Case Study of Malang City Local Program - Riski Amalia; Reza Safitri; Bambang Dwi Prasetyo (GoAcademica Research & Publishing, 2021)
It has been 18 years since the enactment of Law of The Republic of Indonesia Number 32 of 2002 on Broadcasting in Indonesia. During that time, Sistem Siaran Jaringan or commonly known as SSJ became the national broadcasting system. One of the elements in SSJ that differentiates it from the previous broadcasting system is the obligation for private broadcasters in Indonesia to broadcast local programs as much as 10% of their total broadcast hours. The hopes of Law of The Republic of Indonesia Number 32 of 2002 on Broadcasting, diversity of content and diversity of ownership, are often echoed in research related to broadcasting activities as a